Sexual harassment and abuse in sport: The NOC*NSF helpline. (November 2015) - Vertommen, Tine; Schipper-van Veldhoven, Nicolette HMJ; Hartill, Michael J; Van Den Eede, Filip
Following a high-profile case of child sexual abuse in sport in 1996, the Netherlands Olympic Committee and the Netherlands Sports Confederation (NOC*NSF) established a telephone 'helpline' service on sexual harassment and abuse (SHA). In order to expand their understanding of this problem, NOC*NSF maintained written records of incidents reported to the helpline. These records revealed 323 separate incidents for the period 2001 to 2010. This paper presents a descriptive analysis of this data and discusses the findings. We conclude that whilst there are major limitations to working with information gathered in this way, a sustainable telephone 'helpline' can provide a valuable service for the sports community. Whilst official sources of data are known to under represent the scale of sexual abuse, through collaboration with researchers, such services can also generate important information for policymakers.